Human Development and Subnationalism: A Disaggregated Analysis of Indian States: Kerala and Uttar Pradesh - Manika Garg (CMC Senior Theses. 1843., 2018)
This thesis investigates achievements in human development outcomes on health, education, and poverty indicators across Indian states, in order to discern what factors might influence a state’s better orientation toward social policies. After conducting data analysis, the study explains differences in outcomes, as achieved by Kerala and Uttar Pradesh, by building an argument of subnational solidarity and its impact on determining the state’s policy agendas.